Specific versus non-specific exercises for the neck extensor muscles in women with chronic idiopathic neck pain: A randomized controlled trial. (August 2022) - Giménez-Costa, M.; Schomacher, J.; Murillo, C.; Blanco-Hernández, T.; Falla, D.; Lluch, E.
Abstract: Background: Structural and functional impairments of the cervical extensor muscles have been demonstrated in people with neck pain. A global exercise approach targeting all neck extensor muscles has shown positive effects in this population. However, to date, the efficacy of exercises specifically targeting the deep neck extensors has neither been tested nor compared to global exercises for the neck extensors. Objectives: To compare the effects on pain and disability of a specific lower deep neck extensors (SLDNE) versus a general neck extensor (GNE) exercise program in women with chronic idiopathic neck pain. Methods: Fourty-three women with chronic idiopathic neck pain were randomly allocated to either a six-week SLDNE or a GNE exercise program. As primary outcome, neck disability was measured with the Neck Disability Index (NDI). Secondarily, pain intensity (VAS), cervical ROM, pressure pain thresholds (PPTs), cervical and thoracic posture and self-perceived benefit of treatment (GROC) were also measured. Every outcome was measured at baseline and immediately after treatment, except NDI, which was also measured at 6-months follow-up. The GROC was only assessed post-intervention. Results: Both exercise programs lead to reduced neck disability immediately post-intervention (within-group mean difference [MD] = −6.09; 95% Confidence Interval [CI]: 7.75, −4.42 and −4.73; 95%CI: 6.57, −2.91 respectively) and at the 6-months follow-up (−4.47; 95%CI: 6.41, −2.53 and −4.74; 95%CI: 6.50, −2.97), but with no between group differences. Similar results were found for pain intensity post-intervention, with no between group interaction (within-group MD = −20.87 mm; 95% CI: 28.55, −13.19 and −18.00 mm; 95%CI: (−26.24, −9.76) for SLDNE and GNE groups, respectively). GROC improved after both interventions without any between-group difference. Conclusions: A six-week exercise program specifically targeting the lower deep neck extensors lead to comparable outcomes as a general neck extensor exercise program in women with chronic idiopathic neck pain. Highlights: Neck extensors exercise showed positive effects in women with chronic idiopathic neck pain. No difference between specific lower deep and general neck extensors exercises was found. Exercises were not matched to the neuromuscular impairments of each individual.